Land Tenure of Forest Fringe Communities and Their Impact on Deforestation: A Case Study in Soeharto Forest Park - Tri Furi Megawati; Bambang Semedi; Aminudin Afandhi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Soeharto Forest Park is a forest area located in East Kalimantan, Indonesia. Soeharto Forest Park has an area of about 61,840 hectares and is one of the critical forest areas in Indonesia. Soeharto Forest Park primarily serves as a conservation area and nature preservation. It contains high biodiversity, including various species of flora and fauna that are protected. The research methods involve field surveys, structured interviews, and secondary data analysis. Data was collected to understand community land tenure, including tenure rights, land use, and agricultural practices. In addition, deforestation impacts are identified through mapping land cover change and vegetation density analysis. It is just that over time, the connection of the surrounding community with Soeharto Forest Park is very high. Many people use the Forest Park area to become open land. This lasted from 1957 until 2022. The total land area of Soeharto Forest Park that has been opened is 335,994 m2 or 33,6 hectares. Many communities on the outskirts of Soeharto Forest Park that cleared land and used it as settlements, plantations, and rice fields from 1957 to 2022 highlights the deforestation in land use around the area over a long period. These changes reflect social, economic, and policy dynamics that affect local communities and the surrounding environment.